A novel smart handpiece controlled by voice command system - Adam Malik Hamudeng; Nurul Auliya; Andi NT. Sapada; Muhammad N. Rachmat (Journal of Dentomaxillofacial Science, 2021)
Objective: To investigate the possibility of Smart Handpiece" for controlling dental rotational instruments using the voice command system.Material and Methods: This Smart Handpiece has a battery that can be used directly using AC 220V power supply. On the handpiece, a sound sensor that can recognize sound is provided. This sound sensor can receive commands to adjust the rotation speed of the handpiece, adjust the water and wind are released by the handpiece. In order for the tool to work properly we use a microcontroller to be able to carry out its functions when the sound sensor receives signals. Next the microcontroller will execute the programmed commands such as the voice command that can turn on the compressor to adjust the motor rotation and water output on the handpieceResults: According to our study, the Smart Handpiece can work well with the voice command system.Conclusion:  A novel smart handpieces provides promising prospects for use in dental practice